Improving Brand Image, Price and Promotion Through Consumer Purchase Decisions - Ahmad Yusdarwin Waworuntu; Adnan Hasan (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
The study was conducted to determine the impact of brand image, price, and promotion on product purchasing decisions in the Pangkajene, Indonesia. Using primary data from a survey of all consumers conducted during the January to November 2020 sales period. The data were analyzed using the Statistical Product and Service Solutions program; the results indicated that brand image, price perception, and promotion all had a positive and significant effect on product purchasing decisions. Additionally, it was discovered that promotion has a significant impact on purchasing decisions for brand products in Pangkajene, Indonesia.